Distinction the Effectiveness of Therapy Music with Techniques of Relaxation Progressive to Increasing the Quality of Sleep for the Elderly in Banjar Peken Sumerta Kaja Village. - Ni Nyoman Sri Widyastuti (Coping: Community of Publishing in Nursing, 2013)
Degeneration process in elderly impact on the quantity of sleep in elderly which increasingly erduced the quality of elderly sleep. The condition is indirectly can interfere withhealth and causes someone to fall into diseased condition so that it will give rise to new complaints of the elderly. The aim of this research is to find out of the difference efecktivness between music therapy with progressive relaxation techniques for the quality of elderly sleep. This research is one of group quasy experiment. The number of samples used as much as 32 elders. A gathering of the necessary data obtained from sheets of a questionnaire that analyzed with the paired t-test before and after given music therapy with the value of p=0,000 which means that there was increased the quality of elderly sleep, for before and after given progressive relaxation techniques with the value of p=0,000 which means that was increased the quality of elderly sleep to. To know the difference effectiveness between music therapy and progressive relaxation techniques for the quality of elderly sleep,it was seen from the p-value by using independent sample t test analized with scocre 0,000 and the average of increase by using music therapy as much as 5.38 and by using progressive relaxation techniques as much as 2.75 .It Can be concluded that there are a difference effectiveness between music therapy and progressive relaxation techniques for the quality of elderly sleep. Based on these results, it is suggested to the nurses to use music therapy to improve the quality of elderly sleep.